Assessment of Peer Pressure and Sexual Adventurism among Adolescents in Ghana: The Moderating Role of Child-Rearing Practices - Sylvia Eyiah-Bediako (MDPI AG, 2021)
The rationale of this study was to examine the influence of peer pressure on sexual adventurism among adolescents in Ghana, and as well to explore the role of child-rearing practices in this relationship. The study covered adolescents in junior high schools in Ghana within the age range of 12 to 19 years. A sample of 525 adolescents was surveyed to participate in the research using the multistage sampling approach. The main instrument for data collection was a questionnaire. Data gathered were analysed using means and standard deviation, multivariate linear regression, and three-way interaction-moderation analysis. Child-rearing practices and peer pressure significantly and independently predicted sexual adventurism. Parental discipline acted as a significant moderator in the relationship between peer pressure and sexual adventurism. Again, only in the presence of discipline could monitoring and warmth moderate the relationship between peer pressure and sexual adventurism. Based on the findings, parents are encouraged to incorporate reasonable disciplinary measures in shaping their children’s behaviours against sexually deviant activities. Besides, guidance and counselling coordinators should plan and organize programs that centre on reducing the prevalence of peer pressure and sexual adventurism. Conclusions drawn from the study include bringing out a better understanding of the role that discipline and peer pressure play in influencing adolescents’ sexual adventurism.